Evidence-Based Forensic Dentistry - Rai, Balwant; Kaur, Jasdeep; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Recent years have witnessed significant advances in forensic odontology. This book presents basic concepts in the field and describes all the standard examination procedures currently employed in the acquisition of dental evidence. Detailed information is provided on the identification of unknown individuals, the application of forensic dentistry in mass disasters and multiple fatality incidents, the role of dental evidence in child abuse investigations, and the analysis of bite mark evidence. Other features of the book are a series of high-profile cases, clear advice on the writing of legal reports, and discussion of the significance of DNA and oral fluid in forensic odontology. The text is supplemented by numerous high-quality figures, many of them in color. This book will be invaluable for: Dental examiners and pathologists who need to know about the proper handling and evaluation of dental evidence Legal and police science professionals wishing to learn how best to present dental findings in a court of law Dentists who want to use their training and experience in an interesting and challenging way.
Forensic odontology: history, scope and limitations -- Oro-dental identification -- Dental age estimation -- Craniofacial Identification -- Sex determination methods in Forensic odontology -- Tooth Morphology -- Bite Marks: Evidences and Analysis Part-1 -- Bite Marks Analysis: Adobe Photoshop® Part .2 -- Cheiloscopy in identification: Forensic odontology -- Palatal rugoscopy important tool in Forensic odontology -- Forensic oro-dental radiology -- Denture Marking: Forensic odontology aspects -- Different types of light in forensic photography -- Advance technologies in forensic odontology -- Forensic odontology in management of bioterrorism -- Management of Mass disasters: Forensic odontology -- DNA Technology and Forensic odontology -- Pink teeth: an important aspect for Forensic Science -- Role of Dentist and Forensic odontogist in Child abuse case -- Dental Jurisprudence and Ethics -- Oral Fluids and Teeth in Toxicology -- Forensic odontology report.
Keywords: Dentistry; Forensic medicine; Dentistry; Forensic Medicine